¿Fueron los centros de atención móvil para drogodependientes (CAMAD) una solución viable de gestión y planificación? (2020)
This article presents a critical analysis of the management and planning of the Mobile Care Centers for Drug Addicts (CAMAD), based on the review of the Development Plan of Bogotá Humana from 2012 to 2016 and taking into account the public policy for attention and prevention of the consumption and supply of psychoactive substances in Bogota D.C. From the press analysis of different chapters of the Development Plan, it came to the conclusion that the initiative of this government proposal is linked to decreased risk producing psychoactive substances in order to improve the quality of life street dwellers.